Foreign direct investment and performance requirements : new evidence from selected countries (UN New YorkUS, 2003)
Examines the use and impact of performance requirements in four developing countries viz. Chile, India, Malaysia and South Africa. Reviews the use of performance requirements in developed countries. Focuses on performance requirements that are not prohibited by the WTO Agreement on Trade-Related Investment Measures, but may be addressed in various agreements at the bilateral or regional levels.
Keywords: FOREIGN INVESTMENT